Foodborne Pathogens - Recent Advances in Control and Detection 2023
DOI: 10.5772/intechopen.105694
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Foodborne Pathogens and Their Diseases

Abstract: Thousands of foodborne pathogens are causing a great number of diseases with significant effects on human health and economy. Foodborne pathogens can contaminate food items not only during production and processing, but also at the time of storage and transport before consuming. During their growth, these microorganisms are capable of secreting different type of toxins into the extracellular environment. Likewise, other harmful substances can be also released and can contaminate food after breakup of food path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Foodborne infections have become more frequent over time and have now become a serious threat to public health globally, with more than 600 million people getting sick each year as a result [1,2]. Foodborne pathogens are responsible for thousands of infections and they are posing a risk to both the health of humans as well as the general economy due to their negative health effects [3]. A wide range of pathogenic microorganisms are capable of infecting food products throughout the manufacturing and processing processes as well as throughout storage and shipment processes prior to consumption [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Foodborne infections have become more frequent over time and have now become a serious threat to public health globally, with more than 600 million people getting sick each year as a result [1,2]. Foodborne pathogens are responsible for thousands of infections and they are posing a risk to both the health of humans as well as the general economy due to their negative health effects [3]. A wide range of pathogenic microorganisms are capable of infecting food products throughout the manufacturing and processing processes as well as throughout storage and shipment processes prior to consumption [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Foodborne pathogens are responsible for thousands of infections and they are posing a risk to both the health of humans as well as the general economy due to their negative health effects [3]. A wide range of pathogenic microorganisms are capable of infecting food products throughout the manufacturing and processing processes as well as throughout storage and shipment processes prior to consumption [3][4][5]. The widespread intestinal disorders triggered by foodborne human pathogens are estimated to lead to a significant financial and health burden [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Symptoms of foodborne illnesses can range from nausea, vomiting, diarrhea, abdominal pain, fever, and severe dehydration, resulting in organ damage. 4 Common foodborne pathogens, primarily bacteria, include Escherichia coli O157:H7 (E. coli O157:H7), Salmonella Typhimurium (S. Typhimurium), Listeria monocytogenes (L. monocytogenes), Shigella sonnei (S. sonnei), Campylobacter jejuni (C. jejuni), Clostridium perfringens (C. perfringens), and Vibrio parahemolyticus (V. parahemolyticus). Data from the United States (USA) between 2015 and 2019 reported that Salmonella infections, being the most common (18.6%), were responsible for 48% of foodborne illness outbreaks, and others also contributed to these outbreaks.…”
Section: ■ Introductionmentioning
confidence: 99%